9y-7(x-y)-x=

Simple and best practice solution for 9y-7(x-y)-x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y-7(x-y)-x= equation:


Simplifying
9y + -7(x + -1y) + -1x = 0
9y + (x * -7 + -1y * -7) + -1x = 0
9y + (-7x + 7y) + -1x = 0

Reorder the terms:
-7x + -1x + 9y + 7y = 0

Combine like terms: -7x + -1x = -8x
-8x + 9y + 7y = 0

Combine like terms: 9y + 7y = 16y
-8x + 16y = 0

Solving
-8x + 16y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16y' to each side of the equation.
-8x + 16y + -16y = 0 + -16y

Combine like terms: 16y + -16y = 0
-8x + 0 = 0 + -16y
-8x = 0 + -16y
Remove the zero:
-8x = -16y

Divide each side by '-8'.
x = 2y

Simplifying
x = 2y

See similar equations:

| N^2-3+2=0 | | 13x+6-3=12x-3 | | 4(9b+c-5a)-5(a-3c+4b)= | | 33=(3x-8)(7x+4) | | 7(p+7q-13)= | | N^2-13n+40=0 | | 5(6y+12)=6(12y-4) | | 30=-1.2v | | 2x^2+10x-18=0 | | 5(6y+12)=6(12-4) | | -2(4n+4)=2 | | 15x^4-12x^3+3x^2=0 | | y-(-3)=2(x-2) | | (-1)x^3=27 | | 6x+2.72=4.22 | | (1+z)(5z-2)=0 | | 10x+26(x-2)=128 | | 5x+27(x-4)=84 | | 3m+38=9m-4 | | 5m+14=9m-2 | | -6z+2(5-3z)=8(-3z+2)+10 | | 4(p+8q-13)= | | 22-2=6n | | -3k=14-k | | 6y-8(-3)=24 | | 6y-8x=24 | | 5(x+3)=3(7x+3)-2 | | g(x+5)=x^2+2x+3 | | 4x^2+8-77=00 | | 6x+21=2x-1 | | g(-1)=x^2+2x+3 | | g(x)=x^2+2x+3 |

Equations solver categories